2014
DOI: 10.4028/www.scientific.net/msf.782.404
|View full text |Cite
|
Sign up to set email alerts
|

Metallographic Analysis of ECAP Processed Selected Magnesium Alloys

Abstract: Magnesium alloys has been used for a wide variety of applications, namely from the reason of their low density and high strength–to–weight ratio. The properties of magnesium alloys are connected with microstructure that is influenced by metallurgical and technological aspects. Scope of utilisation of foundry magnesium alloys is continuously being extended, so if we want to operate as competitive producers, it is necessary to investigate very actively properties of individual alloys, optimise their chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In [11] was presented strength dependence on the grain size for AZ31 magnesium alloys, with the similar texture, supports that the softening of ECAPed AZ31 alloys (a negative slope) which are typically observed despite the significant grain refinement, is due to the texture modification where the rotation of basal planes occurs towards the orientation for easier slip [12][13][14]. Thus, it can be concluded that the yield strength of the SPDed Mg alloy is determined by the competition of grain size strengthening effect and texture softening effect, and the texture softening depends on the texture type and texture intensity [15].…”
Section: Mechanical Properties Of Ex -Ecap Az31 Magnesium Alloymentioning
confidence: 58%
See 1 more Smart Citation
“…In [11] was presented strength dependence on the grain size for AZ31 magnesium alloys, with the similar texture, supports that the softening of ECAPed AZ31 alloys (a negative slope) which are typically observed despite the significant grain refinement, is due to the texture modification where the rotation of basal planes occurs towards the orientation for easier slip [12][13][14]. Thus, it can be concluded that the yield strength of the SPDed Mg alloy is determined by the competition of grain size strengthening effect and texture softening effect, and the texture softening depends on the texture type and texture intensity [15].…”
Section: Mechanical Properties Of Ex -Ecap Az31 Magnesium Alloymentioning
confidence: 58%
“…The Equal Channel Angular Pressing (ECAP) method is based on the dislocation activities and is configuration during increased deformation degree [3][4][5][15][16][17][18][19]. In Fig.…”
Section: The Principle Of Equal Channel Angular Pressingmentioning
confidence: 99%
“…Microhardness values of 810 MPa and 970 MPa were reached in [17] after hot rolling and additional aging respectively. The WE43 alloy processed by ECAP has 1020 MPa in microhardness according to [18].…”
Section: Resultsmentioning
confidence: 99%
“…Detailed study of the severely plastic deformed structure was realized by using electron microscopy (SEM, TEM, and EBSD) on the microscopes Tecnai G2 F20 and FEI FEGSEM Qanta 3D (Polish Academy of Science, Krakow, Poland), respectively. Detailed procedure description and its experimental verification were presented by Hilšer et al in [20,21].…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…and EBSD) on the microscopes Tecnai G2 F20 and FEI FEGSEM Qanta 3D (Polish Academy of Science, Krakow, Poland), respectively. Detailed procedure description and its experimental verification were presented by Hilšer et al in [20,21]. Tensile properties characterization of the investigated magnesium alloy was carried out with the use of Micro-tensile Tests (M-TT).…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%